2015
DOI: 10.1128/jvi.00354-15
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Zika Virus Infection in Human Skin Cells

Abstract: Zika virus (ZIKV) is an emerging arbovirus of the Flaviviridae family, which includes dengue, West Nile, yellow fever, and Japanese encephalitis viruses, that causes a mosquito-borne disease transmitted by the Aedes genus, with recent outbreaks in the South Pacific. Here we examine the importance of human skin in the entry of ZIKV and its contribution to the induction of antiviral immune responses. We show that human dermal fibroblasts, epidermal keratinocytes, and immature dendritic cells are permissive to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
1,283
4
47

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,059 publications
(1,404 citation statements)
references
References 64 publications
41
1,283
4
47
Order By: Relevance
“…Conversely, ZIKV was shown to bind to TAM but not TIM receptors 23 . It is possible that the looser surface of DENV2 compared to ZIKV could allow more interactions with a wider range of phosphatidylserine-binding receptors.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, ZIKV was shown to bind to TAM but not TIM receptors 23 . It is possible that the looser surface of DENV2 compared to ZIKV could allow more interactions with a wider range of phosphatidylserine-binding receptors.…”
mentioning
confidence: 96%
“…The Asn67 (but not Asn153) glycosylation site in DENV has been shown to be crucial for binding to DC-SIGN (also known as CD209) 22 on dendritic cells. ZIKV, which also interacts with DC-SIGN 23 , does not have this glycosylation site, and therefore could have a different binding mechanism.…”
mentioning
confidence: 99%
“…Members of the Flaviviridae family, including important human pathogens like Dengue, West Nile virus (WNV), hepatitis C virus (HCV), and the recently pandemic Zika virus, all enter via receptor-mediated or clathrin-mediated endocytosis [31,64,65]. HCV, Dengue, WNV and Zika virus then enter late endosomes after Bback-fusion^of ILVs with this compartment, at which point the viral genome is dumped into the cytoplasm [66,67].…”
Section: Viral Manipulation Of Exosomal Pathwaymentioning
confidence: 99%
“…Aedes mosquito deposits the virus in the epidermis and dermis of the bitten host during a blood meal. Skin fibroblasts, immature dendritic cells, and epidermal keratinocytes were found to be highly permissive to infection with ZIKV [18]. Heparan sulfate act as a nonspecific attachment factor of Flaviviruses, as it concentrates viral particles on the cell surface and facilitates their interaction with primary receptors [7].…”
Section: Entry Receptors For Zikvmentioning
confidence: 99%
“…It was reported that DC-SIGN, AXL, Tyro3, and, to a lesser extent, TIM-1, permitted ZIKV entry, with a major role for the TAM receptor AXL. The role of these receptors in ZIKV entry was confirmed by the use of a neutralizing antibody and specific RNA silencing [18]. Virus replication occurs in the cellular cytoplasm [29].…”
Section: Entry Receptors For Zikvmentioning
confidence: 99%